2020
DOI: 10.1002/mus.26863
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography of the median nerve: A mechanical study

Abstract: Background: Shear wave elastography (SWE) shows promise in peripheral neuropathy evaluation but has potential limitations due to tissue size and heterogeneity. We tested SWE sensitivity to elasticity change and the effect of probe position in a median nerve cadaver model. Methods: Ten specimens were used to measure median nerve elasticity under increasing loads using SWE and indentation. Measurements were compared using repeated-measures analysis of variance. Results: Indentation and SWE-based longitudinal ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Various animal models of peripheral neuropathies, such as those associated with metabolic syndrome (Layton et al, 2004), trauma (Zhu et al, 2020) or anti-neoplastic drugs (Bober and Shah, 2015), have shown that peripheral nerve stiffness tends to be higher regardless of etiology. Using ultrasound shear wave elastography, preliminary human studies have demonstrated that shear wave velocity of nerves, a surrogate measure of nerve stiffness (Schrier et al, 2020), increases in both compression (Kantarci et al, 2014) and diabetic (Dikici et al, 2016) neuropathies. However, these clinical investigations focused on a single nerve region and did not account for potential heterogeneity of mechanical changes along the course of peripheral nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Various animal models of peripheral neuropathies, such as those associated with metabolic syndrome (Layton et al, 2004), trauma (Zhu et al, 2020) or anti-neoplastic drugs (Bober and Shah, 2015), have shown that peripheral nerve stiffness tends to be higher regardless of etiology. Using ultrasound shear wave elastography, preliminary human studies have demonstrated that shear wave velocity of nerves, a surrogate measure of nerve stiffness (Schrier et al, 2020), increases in both compression (Kantarci et al, 2014) and diabetic (Dikici et al, 2016) neuropathies. However, these clinical investigations focused on a single nerve region and did not account for potential heterogeneity of mechanical changes along the course of peripheral nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research reveals that diseases such as carpal tunnel syndrome and DPN can cause structural changes, edema within the nerve fascicle and reduction of blood flow, leading to the compression and increase in stiffness of the affected nerve 10,11 , which provide the possibility of diagnosis with SWE. At the same time, some studies have preliminarily confirmed that SWE can objectively reflect the increase of in stiffness of nerve tissue in indentation testing 12 . Yet, for such a new technology, there are relatively few studies on shear wave elastography of peripheral nerves, especially those addressing the methodology and influencing factors of peripheral nerve SWE in healthy people.…”
Section: Preliminary Study On the Influencing Factors Of Shear Wave E...mentioning
confidence: 92%
“…A systemic review revealed the median nerve became stiffer after compression under shear wave elastography quantification [ 7 , 8 ]. Shear wave elastography had high sensitivity to detect changes in median nerve elasticity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%